Comparative efficiency of forming m[4]T[.]G versus m[4]T[.]A base pairs at a unique site by use of Escherichia coli DNA polymerase I (Klenow fragment) and Drosophila melanogaster polymerase -primase complex. - Dosanjh, M.K.; Essigmann, J.M.; Goodman, M.F.; Singer, B. (Biochemistry, 1990)
Synthesis of a 25-mer oligonucleotide template containing O4-methylthymine (m4T) at a unique site is reported. The sequence used is analogous to that studied previously to determine the mutation frequency of O6-methylguanine in vitro and in vivo. The templates containing m4T or unmodified T were used in a primer-extension gel assay to determine kinetic parameters for incorporation by DNA polymerases of dGTP and dATP opposite either m4T or T. Both Escherichia coli DNA polymerase I (Klenow fragment, Kf) and Drosophila melanogaster polymerase alpha-primase complex (pol alpha) were used. On the basis of the Vmax/Km ratios, the pairing of m4T.G was preferred over that of both m4T.A and T.G by more than 10-fold. The two polymerases gave almost identical values for the frequency of formation of all pairs investigated including m4T.G pairs, suggesting that the 3'----5' exonuclease activity of the Klenow fragment does not efficiently edit such pairs. Extension beyond m4T.G was demonstrated with both Klenow and pol alpha. In similar kinetic experiments, bacteriophage T4 DNA polymerase, which has a very high 3'----5' exonuclease activity, allows stable incorporation of G opposite m4T in contrast to G opposite T. This kinetic approach allows quantitation of the mutagenic potential in the absence of alkylation repair and additionally provides qualitative data on mutagenesis that are in accord with our previous in vivo studies showing that replication of m4T causes T----C transitions.